COMPETITIVE POSITION OF THE BANK IN THE BANKING SERVICES MARKET OF UKRAINE - SHIRINIAN, Edvard (Scientific journal «World of Finance», 2024)
Introduction. The competitive position of the bank in the banking services market is defined as the position of the bank in comparison with competitors in the provision of banking services. The Law of Ukraine "On the Protection of Economic Competition" postulates only the maximum market share of any subject by one parameter. The issue of quantitative calculation of the bank’s market position using various parameters and comparison is relevant.The purpose of the article is to develop a new methodology for assessing the competitive position of a banking institution using quantitative parameters of market coverage and performance criteria that determine key aspects of bank activity.The research methodology uses statistical analysis and comparison of market coverage indicators, elements of financial analysis in terms of activity efficiency. The NBU data on each bank, data from open sources, researchers’ publications serve as the information base.Results. We developed a methodology for determining the bank’s competitive position on the banking services market of Ukraine. The number of proposed evaluation parameters and indicators of the bank’s competitive position is eight. An integral indicator of the bank’s competitive position is proposed to determine the bank’s position in comparison with its competitors. The approach was tested on the example of a sample of 5 banks operating in Ukraine. It is shown how the market position can be improved.Conclusions. The approach is aimed at improving the Law of Ukraine "On the Protection of Economic Competition" in terms of determining the competitive position. It shows the direction of competition, the expediency of integration with competitors in order to improve business efficiency and development.